The Role of Market Orientation as a Moderating Variable in the Relationship between Entrepreneurial Orientation and Firm Performance. (Global Business Management Review (GBMR), 2022)
This conceptual paper tries to examine the relationship between entrepreneurial orientation (EO) and firm performance and also the role of market orientation (MO) as a moderating variable. EO and MO are important strategic orientations that can coexist and relate to the firm’s performance but most of the studies which performed these orientations towards firm performance considered as independent variables and carried out separately. This paper also discussed the main dimensions of EO and MO variables and its relation to the firm performance. Finally it will be ended with the conceptual framework and methods that should be used for future study.